Contribution to the genus Phlugiolopsis (Tettigoniidae: Meconematinae) from China - Zheng, Mengjia; Shi, Fuming (Zootaxa, 2024)
This paper reports four new species from Yunnan, Hunan and Guangdong in China, i.e. Phlugiolopsis procera sp. nov., Phlugiolopsis clavata sp. nov., Phlugiolopsis nanlingensis sp. nov. and Phlugiolopsis spina sp. nov. While the females of Phlugiolopsis bispinata Bian & Shi, 2018 and Phlugiolopsis breviproceris Zheng, Shi & Chang, 2023 are described for the first time. All specimens are deposited in the Museum of Hebei University.